Effect of indole-3-butyric acid, putrescine and benzyladenine on rooting and lateral bud growth of Ficus elastica Roxb. ex Hornem leaf-bud cuttings - M. Ghasemi Ghehsareh (Indian Journal of Horticulture, 2023)
An investigation was conducted to study the effects of indole-3-butyric acid (IBA), putrescine (Put) and benzyladenine (BA) on rooting and bud sprouting of leaf-bud cuttings of Ficus elastica Roxb. ex Hornem.. The highest number of roots per cutting (19.00) was obtained with Put 4000 ppm + IBA 4000 ppm and the lowest (4.17) was observed in control. Root length was increased with increasing Put concentrations and decreased with increasing IBA concentration. The highest length (12.17 cm) was observed with Put 4000 ppm and the lowest root length (7.1 cm) with Put 1000 + IBA 4000 ppm. The highest weight of roots (3.49 g) was obtained with Put 4000 + IBA 1000 ppm, and the lowest weight (1.2 g) was observed with control. In spite of the positive effects of IBA on rooting, higher concentrations produced thick and brittle roots, but application of Put improved the roots and led to more acceptable roots. The highest shoot length (30.5 cm) was obtained on cuttings treated with IBA 4000 + Put 4000 + BA 1000 ppm and the lowest shoot length (14.0 cm) was observed at BA 250 ppm treatment that was not significantly different compared to control. The highest number of leaves (6.0) was obtained with IBA 1000 + BA 4000 ppm and the lowest (3) obtained with control and BA 250 ppm. It was concluded that BA positively affected the number of leaves but IBA and Put had no significant effects on this parameter.